BOOSTING MOTIVATION THROUGH BIBLIOTHERAPY TECHNIQUE - SHILHIYA KHAIRI NAFS; ZULKIPLI LESSY (Universitas Islam Negeri Mataram, 2021)
Abstract: This research aims to investigate bibliotherapy services in improving children’s motivation who suffer from chronic illness. The argument in the study asserted that bibliotherapy has a positive effect on children. This is eventually an indication that change of condition improved as shown by the children with chronic illness at Rumah Harapan Indonesia (RHI) Bandung. Participants in this study consist of 10 children with chronic disease who are from out of town to consciously seek medical treatment and stay at RHI. With the use of the descriptive qualitative method, this study inferred that bibliotherapy not only helped heal the children who had difficulty in socializing with peers, feeling tired, bored with circumstances, despair, fear, and experiencing slow growth and development, but also made them have emotional and mental maturity. This research significantly contributes to the further development of some innovative ways to optimize bibliotherapy services for children with chronic diseases.